2008
DOI: 10.1016/j.cellbi.2007.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide Elk‐1 suppresses the tumorigenicity of human hepatocellular carcinoma cells

Abstract: In previous studies, we showed that reducing Ets-like protein-1 (Elk-1) expression inhibited protein kinase C alpha (PKC alpha) expression and decreased cell migration and invasion in human hepatocellular carcinoma (HCC). In this study, we have investigated the role of Elk-1 in tumorigenesis. SK-Hep-1 HCC cells were transfected with the ElK-1 antisense oligonucleotide (ODN). In the pretreated cells we detected a reduction of mRNA level using RT-PCR. The inhibitory rate of cell growth was measured by MTT assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
(35 reference statements)
3
18
0
Order By: Relevance
“…Although the function of Elk-1 in human cancer has not been clearly established, initial results indicate that downregulation of Elk-1 suppresses the tumorigenicity of human hepatocellular carcinoma cells. 50 Although Bdp1 expression is not regulated directly by Elk-1, the resulting Elk-1-mediated change in TBP expression governs Bdp1 promoter activity and cellular Bdp1 concentrations, demonstrating that alterations in cellular TBP levels modulate Bdp1 expression but not Brf1. 8 …”
Section: Signaling Events During Dysregulation Of Pol III Genesmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the function of Elk-1 in human cancer has not been clearly established, initial results indicate that downregulation of Elk-1 suppresses the tumorigenicity of human hepatocellular carcinoma cells. 50 Although Bdp1 expression is not regulated directly by Elk-1, the resulting Elk-1-mediated change in TBP expression governs Bdp1 promoter activity and cellular Bdp1 concentrations, demonstrating that alterations in cellular TBP levels modulate Bdp1 expression but not Brf1. 8 …”
Section: Signaling Events During Dysregulation Of Pol III Genesmentioning
confidence: 98%
“…49 Furthermore, these changes regulate c-Jun levels and its activity, which in turn increase proliferation rates. 50 The regulation of Pol III gene transcription by JNKs through its effects on TBP and its associated factors, Brf1 and Bdp1, constitutes a mechanism by which it controls the proliferative capacity of cells.…”
Section: Signaling Events During Dysregulation Of Pol III Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that JNK-mediated alterations in cellular TBP expression dictate the proliferation rates of MEFs (19). Furthermore, these changes in TBP concentrations regulate c-Jun levels and its activity, which have been shown to drive the proliferation rates of MEFs (29). Our finding that the JNKs regulate RNA pol IIIdependent transcription through its affects on TBP and its associ- ated RNA pol III factors identifies a mechanism by which it controls the proliferative capacity of these cells.…”
Section: Discussionmentioning
confidence: 85%
“…JNK-mediated regulation of all 3 TFIIIB subunits is orchestrated through Elk-1. Although a role for Elk-1 in human cancer has not been clearly established, initial results indicate that reduced expression of Elk-1 suppresses tumorigenicity of human hepatocellular carcinoma cells (29). While Bdp1 expression is not directly regulated by Elk-1, the resultant Elk-1-mediated change in TBP expression serves to regulate Bdp1 promoter activity and cellular Bdp1 concentrations.…”
Section: Discussionmentioning
confidence: 97%